Construction of novel super microporous silica adsorbents using pluronic triblock copolymer as template towards desulfurization from fuel. (15th February 2023) - Zhao, You; Zhao, Wenkai; Xiao, Yonghou; Zhao, Qidong; Li, Chengbin; Dong, Xiaoying; Lu, Shengnan
Graphical abstract: Highlights: Novel supermicroporous silica with bimodal micromesopores was synthesized. A pluronic triblock copolymer of small molecular weight was used as template. Desulfurization performance was remarkably enhanced due to super micropore. Super microporous silica exhibited excellent regeneration performance. Abstract: As an efficient fuel purification technique, adsorption desulphurization has attracted wide attention. Silicon oxide has been verified as a promising candidate for adsorption desulfurization reagent due to the advantages of stable structure, inexpensiveness and accessibility. However, its adsorption desulfurization performance is always weakened by the limited pore channel size leading to pore diffusion resistance over the traditional microporous silicon oxide, and it suffers from the poor shape selectivity of mesoporous silicon oxide as well. In this work, we successfully prepared a novel super microporous silica material (SMS) with a unique bimodal micro-mesoporous pore size distribution mainly around 1.2 nm, 1.6 nm and 1.8 ∼ 3.5 nm, using a pluronic triblock copolymer with approximately an average molecular weight of 3858 as template by hydrothermal synthesis. The SMS possessed the characteristics of Ia3d cubic phase and super microporous as well as mesoporous silica structure, according to the X-ray diffraction characterization as well as nitrogen adsorption isotherms. The SMS could effectively reduce the diffusion resistance and exhibit improved shape selectivity compared to microporous or mesoporous silicon oxide, respectively, by virtue of its bimodal micro-mesoporous pore size distribution. Under an optimized crystallization temperature of 100 °C for 24 h, the as-synthesized SMS displayed a notable desulfurization performance with a breakthrough capacity of 0.122 mmol S/g benzothiophene, which was significantly superior to that of traditional mesoporous silica KIT-6 (0.04 mmol S/g). Furthermore, the desulfurization performance of SMS adsorbent was not significantly reduced after three cycles of regeneration. The SMS exhibited high desulfurization capacity, easy regeneration and satisfactory regeneration performance, and it could be applied in adsorptive desulfurization technology.